Baby Genius World / Rohani Abdullah ... [et al.] - Abdullah, Rohani; Helmi, Nordalilah; Md. Som, Shanizan; Ahmad Raduan, Haryanti
Children is the most valuable gift from Allah S.W.T. Every single baby really need an attention, love and affillation from their parents. So to show how concern the parents would be, they can try to give their babies the best they can. The existence of the Baby Genius World as an outlet in the middle of Alor Setar town can fulfill the needs and wants by the parents. Consequence of that people are busy with their current job and the increasing of the working mother, then it ,will put some fixed time to search for baby products and others also. Therefore the demand for the one stop baby center is increasing because by having this service, the preparation will be easy and smooth to handle because our market segmentation that focus for a new born babies and for the babies up to age three. In fact, our location with Is in City Plaza, Alor Setar is a strategic location completed with all facilities such as bank, bus stop, car parking lots, supermarket, restaurant, good telecommunication networking and near the main road. Market demand on this business is high due to increasing in the married structure and also the increasing numbers of new born babies in our country. Baby Genius World believe that we will have a stable market for our business based on the data of population from Jabatan Perangkaan. A desire to have a special care for their babies also increase as the standard of living is also increasing from time to time.